Understanding partial protection and HIV risk and behavior following voluntary medical male circumcision rollout in Kenya. - L’Engle, K.; Lanham, M.; Loolpapit, M.; Oguma, I. (Health Education Research, 2014)
In the midst of scaling up voluntary medical male circumcision (VMMC) in Kenya, there is concern that men do not adequately understand that circumcision provides only partial protection against HIV. The study goal was to determine men’s understanding of partial protection, perceptions of HIV risk before and after VMMC and use of protective measures following VMMC. In-depth interviews with 44 men aged 18–39 years recently circumcised or planning to undergo VMMC were conducted in two urban and rural districts in Nyanza Province, Kenya. Participants described partial protection as the need to continue using other HIV protective measures such as condoms, with numbers such as a ‘60 percent protection’ or ‘not 100 percent protection’, and described how circumcision reduces HIV transmission such as reduced penile bruising or bleeding. Most said their HIV risk before VMMC was high and that VMMC would reduce their risk moderately. Participants demonstrated good understanding of partial protection and there was little suggestion of risk compensation following VMMC.